Influence of rice husk biochar and inorganic fertilizer on soil nutrients availability and rain-fed rice yield in two contrasting soils - Oladele, S.O.; Adeyemo, A.J.; Awodun, M.A. (Geoderma, 2019)
The co-application of biochar and inorganic N fertilizer has been shown to be a sustainable and environmental friendly technology for the improvement of soil fertility and crop yield. However, their interactive effects on nutrient availability and rain-fed rice productivity in contrasting soil types in the tropics have been scarcely studied. A field study was set up to investigate the effects of rice husk biochar and N-fertilizer applications at different rates on rain-fed rice yield and soil nutrient distribution in the 0–20 cm soil layer. Biochar was applied at four rates; 0, 3, 6, and 12 t/ha−1, in combination with N fertilizer (urea) applied at four rates; 0, 30, 60 and 90 kg/ha−1 to two different soil types (sandy clay loam Oxic-Paleustalf and sandy loam Oxic-Paleustult). In the Oxic-Paleustaif, biochar × N-fertilizer interaction significantly (p < 0.05) enhanced rain-fed rice yield and yield components such as number of panicles/m2 by 71%, filled spikelet (%) by 24%, grain yield (t/ha−1) by 78%, straw yield (t/ha−1) by 74% and 1000 grain weight (g) by 16% when compared to the control. In the Oxic-Paleustult, interaction between biochar and N-fertilizer significantly (p < 0.05) increased number of panicles/m2 by 73%, filled spikelet (%) by 24%, grain yield (t/ha−1) by 83%, straw yield (t/ha1) by 68% and 1000 grain weight (g) by 13% in the when compared to the control. Leaching of soil nitrate (NO3-N) was mostly reduced in the Oxic-Paleustalf, while soil pH, soil organic carbon (SOC), total nitrogen (TN), available P and K content at the soil depth of 0–10 cm were significantly (p < 0.05) increased in both soil types. The result from this study suggest that biochar amendment and N fertilization have the potential to enhance rain-fed rice productivity and soil nutrient availability, while minimizing nitrate (NO3-N) leaching. •Combination of biochar and inorganic fertilizer enhanced rain-fed rice productivity.•Soil nutrient availability was increased by biochar and inorganic fertilizer interaction.•Soil Nitrate (NO3-N) leaching was reduced by biochar amendment.•These effects were more evident in the Alfisol than in the Ultisol.